Let's review Suzie's solution step by step, starting with the original equation:
\[ 9x - 5 = \frac{1}{4}(16x + 60) \]
- Step 1: Distributing \( \frac{1}{4} \)
Suzie's first step is to distribute \( \frac{1}{4} \). The correct distribution should be: \[ \frac{1}{4}(16x + 60) = \frac{1}{4} \cdot 16x + \frac{1}{4} \cdot 60 = 4x + 15 \] Therefore, the equation \[ 9x - 5 = 4x + 15 \] is what she should have obtained, not \( 9x - 5 = 4x + 60 \).
- Step 2: Subtracting \( 4x \)
Since Step 1 was incorrect, this step follows the incorrect equation. Instead of subtracting \( 4x \) from both sides resulting in: \[ 5x - 5 = 60 \] it should have resulted in: \[ 5x - 5 = 15 \]
- Step 3: Adding 5
Again, since the equation was wrong, moving to this step is also based on an incorrect premise: \[ 5x = 15 + 5 \Rightarrow 5x = 20 \]
- Step 4: Dividing by 5
Finally, this step is based on the incorrect equation: \[ x = \frac{20}{5} = 4 \]
Conclusion
Suzie made a mistake in Step 1 - she should have distributed the \( \frac{1}{4} \) correctly to both terms, including the \( 60 \), resulting in \( 15 \) instead of \( 60 \).
Thus, the correct conclusion is: Suzie made a mistake on Step 1 - she should have distributed the 1/4 to 60 as well.